THE SIGNIFICANCE OF ELLIPSIS IN THE STRUCTURES OF THE TWO POEMS BY AHMED SHAWQI AND TAMIM AL-BARGHOUTI - Hassan, Mohammed; Ahmed, Zirvan (Humanities Journal of University of Zakho, 2025)
The discussion of ellipsis is a phenomenon categorized by its emergence in inconspicuousness and its existence in absence. It is difficult to clasp due to its numerous locations and several stimuli. It gives the text semantic intensity, contributes to the production of meanings through reliance on context, and opens the way for clarifications produced by the recipient. This style is considered one of the linguistic phenomena that has many semantic benefits and contributes to achieving brevity and eloquence. It is an expression of omitting part or all of a speech for evidence or a clue. It occurs frequently in Arab speech when ambiguity is removed, and it is a common style in Arabic poetry. Ellipsis is not only a reduction in words and sentences, but it also carries deep-rooted semantic meanings. This research is a modest effort to study and analyze this phenomenon in the two Burdahs (Ahmed Shawqi and Tamim Al-Barghouthi). We studied this style by mentioning the methods of removal that appeared in the two Burdahs, such as removing words and sentences, including the deletion of the subject, predicate, verb, and agent, the deletion of the conditional clause, and the deletion of the surplus, which includes the described and the adjective, the noun and the noun complement, and the state. We presented evidence from the verses that appeared in them and analyzed them to understand the style of both poets in how they employed this style in the service of constructing linguistic structures. We found out that Ahmed Shawqi focused greatly on deleting words, while Tamim Al-Barghouthi tended greatly towards deleting sentences. These differences reflect the special artistic vision of each poet. Also, we tended to mention the semantic values ​​of deletion and how to provide the verses and meanings with semantic and artistic charges through this style within the two poems.